SŁOTowskie refleksje praktykami wywołane, czyli o tym, kiedy w szkole będą DZIECI - Bednarkowa, Wiga (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
In the text I present a modified way of evaluating student pedagogical practices, based on one of the oldest methods of strategic analysis SWOT – Strengths, Weaknesses, Opportunities, Threats. I also refer to its originals – SOFT – Satisfactory, Opportunity, Fault, Threat. First of all however, I propose to use the strategy/tool SWET to make reflection on the practices and to analyze their course: what was/is Super about practice (deserves a praise)-; what was/is Wretched (deserves a scoundrel)-; what the point about Enclosure of teachers and their Transgressions. However, the main goal I set myself to write this text is – apart from explaining what SWET’s triggers reflection after practice – to encourage the introduction of Good Practice Schools, the value of which arises from the synergy of cooperation of all actors in the educational scene, Teachers of schools and kindergartens and the replacement of bureaucratic control of practices through opened evaluation of them.
Keywords: evaluation; learning methods; student internship; SWOT analysis; transgressions